2002
DOI: 10.1002/humu.9023
|View full text |Cite
|
Sign up to set email alerts
|

A common frameshift mutation and other variants in GJB4 (connexin 30.3): Analysis of hearing impairment families

Abstract: Mutations in GJB1, GJB2, GJB3 and GJB6 are involved in hearing impairment. GJB2, GJB3 and GJB6 are also mutated in patients with hyperproliferative skin disorders. The human GJB4 gene has been deduced in silico and a mutation in a family with erythrokeratodermia variabilis has been reported. We describe here the analysis of the GJB4 gene in hearing impairment patients and control subjects. We have identified a common (4%) frameshift mutation (154del4) in GJB4 in both affected and hearing subjects, one patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…At least six Cx genes (Cx26, Cx29, Cx30, Cx30.3, Cx31 and Cx43) are known to be involved in human genetic deafness (Kelsell et al 1997;Xia et al 1998;Grifa et al 1999;López-Bigas et al 2002;Yang et al 2007;Wang et al 2010). The proteins they encode are located in gap junction-rich regions of the cochlear duct, suggesting that all six connexin proteins are essential components of gap junctions.…”
Section: Introductionmentioning
confidence: 99%
“…At least six Cx genes (Cx26, Cx29, Cx30, Cx30.3, Cx31 and Cx43) are known to be involved in human genetic deafness (Kelsell et al 1997;Xia et al 1998;Grifa et al 1999;López-Bigas et al 2002;Yang et al 2007;Wang et al 2010). The proteins they encode are located in gap junction-rich regions of the cochlear duct, suggesting that all six connexin proteins are essential components of gap junctions.…”
Section: Introductionmentioning
confidence: 99%
“…The proportions of carrier variants for GJB2, GJB3, GJB4, GJC3, and GJA1 were 7.91% (20/253), 4.35% (11/253), 3.56% (9/253), 4.74% (12/253), and 0.40% (1/253), respectively. Twenty-six diVerent variants of the CX gene family were observed, of which 17 were novel variants and the rest were presented in previous reports, including 3 GJB2 variants (c.235delC, c.368C > A, and c.11G > A), 4 GJB4 variants (c.64C > T, c.109G > A, c.292C > T, and c.370C > T) and 2 GJC3 variants (c.*+2T > G, c.781 + 62G > A) (Park et al 2000;Wang et al 2002Wang et al , 2010López-Bigas et al 2002;Hwa et al 2003;Yang et al 2007). Of the 26 variants, 19…”
Section: Study Populationmentioning
confidence: 99%
“…Less frequently encountered are mutations in other CX genes, such as GJB6, GJB3, and GJB1 (Grifa et al 1999;Xia et al 1998;BergoVen et al 1993;Liu et al 2000). In addition, few studies have been conducted on the correlation of variants in the GJB4 (López-Bigas et al 2002;Yang et al 2007), GJA1 (Yang et al 2007) and GJC3 gene (Yang et al 2007;Wang et al 2010), and its phenotype in patients with nonsyndromic hearing loss. In current study, a genetic survey was made on 373 Taiwanese individuals, 253 with nonsyndromic deafness and 120 (Wang et al 2010).…”
Section: Prevalence Of Cxs Gene Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in connexin-26 (Cx26), connexin-30 (Cx30), connexin 30.3 (Cx30.3) and connexin-31 (Cx31) are linked to both non-syndromic and syndromic deafness (Denoyelle et al, 1997;Kelsell et al, 1997;Zelante et al, 1997;Xia et al, 1998;Grifa et al, 1999;Lopez-Bigas et al, 2001, 2002b. Electrophysiological studies of Xenopus oocytes expressing different connexin mutants revealed that HI-associated Cx26 mutants failed to generate intercellular conductance (White et al, 1998;Bruzzone et al, 2001Bruzzone et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%